Batik through Creative Knowledge - Shaari , N. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Textiles play an important part in creating and reflecting the cultural identity of many cultures throughout the world. This can also clearly identify through batik designs and its usage. A characteristic of the culture of batik communities has been its tendency towards cultural appropriation. Much of batik designers engage commonly appropriate imagery and styles based on their environment, culture experience and cultural objects. Recently, the appropriate aspects of batik designs not only reflects the culture identity but as part of contemporary reality. The very fact that batik making has survived and developed as a form of modern arts and crafts which demonstrates batik’s potential for long term resilience. As we have seen, today’s batik owes a significant part of its fame to innovations and changes since the last century. This modern development of batik that has given birth not only increases our understanding of batik original traditions, however semantic values extent its artistic appearances. In this paper will consider several elements of creative knowledge among the indigenous communities who developed batik as product of identity. The ‘IK’ creativity is meaningful both tradition and modernity in batik designs as this creative knowledge may leads to sustainable the batik crafts in our contemporary life